è¥¿åŠ çœå¤ç”¸å¸‚å¹¼å„¿å›æ±‰è¯æ•™å¦çŽ°çŠ¶åˆ†æž - (F13110013), Mukarramah; Thamrin, Lily; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
The object of research was the Sunshine Kindergarten in Pontianak, through the questionnaire, interview and observation in the two aspects : first, the condition of teaching mandarin in Sunshine Kindergarden in Pontianak, in this aspect, the writer described the background of kindergarten and Mandarin language curriculum, the academic conditions of Mandarin language teachers, teaching instruments, methods and content of Mandarin language teaching. Second, the problems occured during on the process of teaching and their solutions. From the results of research, it can be concluded that the condition of the Mandarin language teaching in Sunshine Kindergarten was good, but there were still some problems found in the teaching and learning processï¼Œespecially students in the teaching process of attention problems. It means, Mandarin language teachers must continuously develope and improve the quality of teaching. Keywords: mandarin teachingÂ Â Â  kindergadenÂ Â Â Â  conditionÂ Â Â  problemÂ æ‘˜è¦ï¼šç¬”è€…ä»¥å¤ç”¸å¸‚é˜³å…‰å¹¼å„¿å›ä½œä¸ºç ”ç©¶å¯¹è±¡ï¼Œé€šè¿‡è°ƒæŸ¥ã€é‡‡è®¿å’Œè§‚å¯Ÿä¸¤ä¸ªæ–¹é¢ï¼Œç¬¬ä¸€ï¼Œé˜³å…‰å¹¼å„¿å›æ±‰è¯æ•™å¦çŽ°çŠ¶ï¼Œè¿™æ–¹é¢é‡Œç¬”è€…ä»”ç»†åœ°è¯´æ˜Žäº†æœ¬å¹¼å„¿å›çš„èƒŒæ™¯ä¸Žæ±‰è¯è¯¾ç¨‹ã€æ•™å¸ˆæ–¹é¢ã€å¦ç”Ÿã€è€å¸ˆä½¿ç”¨çš„æ•™å¦æ³•å’Œæ•™å¦è¿‡ç¨‹ã€‚ç¬¬äºŒï¼ŒäºŽæ±‰è¯æ•™å¦è¿‡ç¨‹ä¸ç»å¸¸å‡ºçŽ°çš„é—®é¢˜åŠè§£å†³æ–¹æ³•ã€‚ä»Žåˆ†æžç»“æžœï¼Œç¬”è€…å¾—åˆ°çš„ç»“è®ºï¼šå¹¼å„¿å›æ±‰è¯æ•™å¦çŽ°çŠ¶ä¸é”™ï¼Œåªä¸è¿‡ï¼ŒäºŽæ±‰è¯æ•™å¦ä¸è¿˜å˜åœ¨å¦ç”Ÿæ–¹é¢é—®é¢˜ï¼Œç‰¹åˆ«æ˜¯åœ¨æ•™å¦è¿‡ç¨‹ä¸å¦ç”Ÿæ³¨æ„åŠ›çš„é—®é¢˜ã€‚è¿™æ„å‘³ç€ï¼Œæ±‰è¯æ•™å¸ˆå¿…é¡»ä¸æ–åœ°åˆ›æ–°è€Œæé«˜å¹¼å„¿å›çš„æ±‰è¯æ•™å¦è´¨é‡ã€‚ å…³é”®è¯ï¼š æ±‰è¯æ•™å¦ å¹¼å„¿å› çŽ°çŠ¶ é—®é¢˜